Re-enacting Mathematics Values through Cultural Symbols - Ali, Clement Ayarebilla (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2023)
More attention and concentration are paid to cognitive and psychomotor than affective learning of mathematics. The problem may have arisen from the symbolic nature of mathematics values which makes it difficult to understand. Another loophole could have popped up from teachers’ perceptions that mathematics values have little relationship with cultural symbols in the classroom, as well as in affective values. In this study, the researcher explored five prominent mathematics values of respect’, ‘commitment to excellence’, ‘truth and integrity’, ‘teamwork’, and ‘equity’ through cultural symbols, called ‘Adinkra’. With a case study design involving ten student teachers, the researcher assembled over 60 Adinkra symbols. The student-teachers then selected and matched at least five of the symbols that fall into each of the five values and analyzed their values. In five separate tables, the results showed that ‘respect’ ranked highest, and was closely followed by ‘commitment to excellence’, and ‘truth and integrity’. The least values were ‘teamwork’ and ‘equity’. Having given this culturally responsive pedagogy, it was recommended that many more cultural symbols should be explored to equip teachers and students to apply mathematics values for life-long learning.